Endangered with High Dispersal Abilities: Conservation Genetics of Himantoglossum metlesicsianum (Teschner) P. Delforge (Orchidaceae) in the Canary Islands - Rocío González Negrín; Victoria Eugenia Martín Osorio; Pedro A. Sosa; Priscila Rodríguez-Rodríguez (Plants)
Himantoglossum metlesicsianum is a threatened orchid with low population numbers and fragmented distribution, present in four of the Canary Islands. This study focused on assessing the genetic variability and population genetic structure of the natural populations known to date, identifying those characteristics of the species that condition the flow and genetic variation. For that purpose, we collected samples from eight sites in its distribution range and developed 14 polymorphic microsatellite markers. Despite its rarity, this orchid presents high levels of genetic diversity and a homogeneous population structure, characterised by a low degree of genetic differentiation and patterns consistent with high genetic connectivity among populations. Our results suggest that the species might show dichotomy in seed dispersal, combining long- and short-distance events. In addition, it is possible that pollen cross-pollination (pollinia) between adjacent sites may also be involved. In conclusion, these findings reveal unexpectedly high genetic diversity and connectivity among populations, despite the species’ rarity and fragmented distribution, highlighting key biological traits that should be considered in future conservation and recovery plans.